Green Robusta Coffee Bean Extract (GRCBE) inhibits bone loss in wistar rat models of Lps P. gingivalis and NiTi wire-induced experimental periodontitis - Dessy Rachmawati; Tantin Ermawati; Nanda Innayatur Rahmatillah; Nurwandani Meylina; Novia Yolanda Safitri; Rina Sutjiati; Ineke D.C. Jansen (Elsevier, 2024)
Oral exposure to alloys frequently leads to negative reactions, both in the immediate area and across the body. The usage of coffee extracts is anticipated to enhance cellular function by counteracting the effects of pro-inflammatory signals that are involved in chronic inflammatory responses triggered by inflammatory agents like bacteria and metal ions. The objective is to develop a new approach using an extract obtained from Robusta coffee beans as an anti-inflammatory substance, which may have therapeutic benefits in preventing bone loss in Periodontitis Rat. The main cause is primarily attributed to the existence of metals and LPS P. gingivalis in the oral cavity. Methods. A randomized controlled trial was conducted, enroling 35 male Wistar rats that were divided into 7 groups and used as the experimental animals. Groups 1-4 consisted of rats that did not receive any therapy, while groups 5-7 comprised rats that were treated with GRCBE. The rats were subjected to decapitation after 14 days. The Green Robusta Coffee bean extract (GRCBE) was derived from the unprocessed green beans of Javanese Robusta coffee. We discovered in prior experimental experiments that GRCBE at a concentration of 500 mg/ml can inhibit the progression of periodontitis in rats. The substances used to cause inflammation and immune system impairment were NiTi wire and LPS P. gingivalis. Immunohistochemistry was used to assess the expressions of OCN, BMP2, and COX-2. Results. The simultaneous exposure of P. gingivalis lipopolysaccharide (LPS) and NiTi wire in rats led to an upregulation of OCN and BMP2 expression, while the expression of COX-2 reduced. The administration of GRCBE resulted in a steady drop in pro-inflammatory biomarkers, specifically OCN and BMP2, while the anti-inflammatory biomarker COX2 rose. In conclusion. In the field of dentistry, the coexistence of P. gingivalis LPS and metallic biomaterials can influence the occurrence of alveolar bone resorption in a rat model of periodontitis. GRCBE exhibits potential as an innovative approach for reducing periodontitis induced by the simultaneous activation of metal and LPS P. gingivalis. In this setting, it has the potential to be employed as an anti-inflammatory remedy.